Relasi Pemerintah dan Masyarakat dalam Menanggulangi Dampak Pandemi Covid-19 pada Penduduk Miskin di Kota Tasikmalaya - Hendra Gunawan; Faisal Fadilla Noorikhsan; Hilal Ramdhani (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
The community's economic downturn caused by the COVID-19 pandemic is a real event that occurred in the City of Tasikmalaya, this condition directly deepens the level of poverty in the City of Tasikmalaya. The existence of an economic recession is one form that is often encountered due to the COVID-19 pandemic. This study aims to examine the relationship between government and society in tackling poverty in the city of Tasikmalaya. A qualitative approach with a case study method is used in this study, data collection techniques using observation, documentation, and interviews and data analysis using data reduction, data presentation, and drawing conclusions. This study uses the theory of structural change which explains that economic changes occur in the community due to a shift from the agricultural sector to industry, this condition indicates that the relationship between government and society is intended to be able to create an economic structure that is able to prevent and overcome poverty. The results of the study show that the government and community relations have not been effective in tackling the impact of the COVID-19 pandemic which has an impact on invalid data on the poor in Tasikmalaya City, community empowerment that has not been optimal, and the vulnerability of women in the category of poor people. These findings indicate the urgency of government-community relations that are carried out systematically and sustainably in all areas in the City of Tasikmalaya so that the government gets valid data on the number of poor people that is used as the basis for making policies regarding community empowerment as a form of relationship between the government and the community.